SOME CHARACTERIZATIONS OF WEAKLY* m-CONTINUOUSMULTIFUNCTIONS - Al-Asadi, Bassam Jabbar J; Al-Ramadhan, Umilkeram Q (Al-Nahrain Journal of Science, 2010)
In this paper we introduce some characterizations of weakly * -m -continuous multifunctions and some results about strongly-m-continuous multifunctions.